Operation requirements for V2X communication of PLMN - Zhengwen CHEN (Dianxin kexue)
Two kinds of V2X technology were introduced briefly and several typical V2X use cases were listed.It was suggested that V2X applications should be deployed with vehicular active safety function firstly.Based on V2X communication of PLMN，operation requirements were provided，including identity authentication，communication function，interoperation of communication，interface with road transport system，operation and maintenance， especially including ideas of delivering identity certifications and measurement messages.